Humoral Effect of SARS-CoV-2 mRNA vaccination with booster dose in solid tumor patients with different anticancer treatments - Piubelli, Chiara; Valerio, Matteo; Verzè, Matteo; Nicolis, Fabrizio; Mantoan, Carlotta; Zamboni, Sonia; Perandin, Francesca; Rizzi, Eleonora; Tais, Stefano; Degani, Monica; Caldrer, Sara; Gobbi, Federico Giovanni; et al. (Frontiers in Oncology, 2023)
Introduction Cancer patients are at risk for serious complications in case of SARS-CoV-2 infection. In these patients SARS-CoV-2 vaccination is strongly recommended, with the preferential use of mRNA vaccines. The antibody response in cancer patients is variable, depending on the type of cancer and antitumoral treatment. In solid tumor patients an antibody response similar to healthy subjects has been confirmed after the second dose. Only few studies explored the duration of immunization after the two doses and the effect of the third dose. Methods In our study we explored a cohort of 273 solid tumor patients at different stages and treated with different anticancer therapies. Results and Discussion Our analysis demonstrated that the persistence of the neutralizing antibody and the humoral response after the booster dose of vaccine was not dependent on either the tumor type, the stage or type of anticancer treatment.